BIOLOGY AND FISHERY OF SILVERBELLY LEIOGNATHUS DUSSUMIERI (VALENCIENNES) FROM GULF OF MANNAR - James, P S B R; Badrudeen, M (Indian Journal of Fisheries, 2011)
•Length-weight relationship of mate and female L. dussumieri was found tobe different. Within femallesi, the SimirMure, maturing, mature and spent-recoveringfemales differ from one another in the length-weight relationship. Males weighcomparatively less than females. Among the females, immature, maturing and spentrecoveringfemales weigh more than mature females. This species mainly spawnsduring April>-Maiy and November-December, Minimum sfefe of maturity for maleswere found to be 78 mm and for females 83 mm. Generally, females predominateover males in the commercial catches. The counts of mature ova ranged from 805to 41683 per female. The fecundity-length relationship has; beea studied by threediffrent formulae and it was found that fecundity is better related; to direct cubeof length.